Fisheries selectivity and annual exploitation of the principal species harvested in a data-limited artisanal fishery at a remote atoll in French Polynesia. (1st August 2019) - Filous, Alexander; Lennox, Robert J.; Clua, Eric E.G.; Danylchuk, Andy J.
Abstract: Artisanal fisheries are critically important to food security and economic opportunity in coastal communities throughout the developing world. However, the dynamics of these fisheries are poorly understood, and a basic understanding of the gear types and species harvested, is required to promote effective fisheries management. To this aim, we surveyed artisanal fishers at Anaa atoll from May 14th, 2016 to May 19th, 2017 and described the selectivity and exploitation of the fishery's dominant species. The harvested marine life included 98 species from 31 families, which were captured with seven gear types including artisanal fish traps, monofilament nets, spear guns, handlines, pole and line, hand, and harpoons. Bonefish ( Albula glossodonta ) were the most abundant species and comprised 25% of the overall catch, followed by Chaetodon auriga, Kuhlia sandvicensis, Lutjanus fulvus, and Chanos chanos . Artisanal fish traps and spearguns harvested a higher proportion of overexploited fishes, captured a more diverse range of species, and removed the most biomass from the atoll. An analysis of the size distribution of harvested fishes, with length-based catch curves, indicates that species with high natural mortality rates such as Chanos chanos and Selar crumenophthalmus were underexploited. While in contrast, slow growing, late maturing, and long-lived species such as Naso lituratus and Epinephelus polyphekadion were overexploited. The results of this research provided the community with the basis for making local management decisions regarding their fisheries resources, including the development of an Educational Managed Marine Area and a seasonal closure of the artisanal trap fishery to allow for movement, predominantly A. glossodonta during their offshore spawning migrations. Highlights: We described the fishery selectivity and species exploitation on Anaa atoll. 98 species from 31 families, were captured with seven gear types. Albula glossodonta comprised 25% of the overall catch. Short-lived species were underexploited, and long-lived species were overexploited. This research helped the community create an Educational Managed Marine Area.